Removal of cadmium from aqueous solution using pleurotus ostreatus as biosorbent / Afiza Abdullah Suhaimi - Abdullah Suhaimi, Afiza (2008)
Removal of cad mium from aqueo us solution using Pleurotus ostreatus as biosorbent was studied. The study was foc used on the eva luation of the impact of amount of biosorbents. pH. and contact time and cadmium concentration on cadmium (ii) ions removal from aqueous solution using Pleurotusus ostreatus as biosorbent and continued with the adsorptio n isotherms and kinetics determ ination . The optimum percent age removal value was found as 86% with the amount of 0.5 g of Pleurotusus ostreatus biosorbent. Optimum percentage uptake was found to occur at acidic equilibrium reached after 10 minutes contact time with 89% and of 4.5 mg/g respectively. Pleurotusostreatus biosorbent removed 85% of cadmium (11) at a concentration of 10 mg/L cadmium (II ) ion s . The optimum uptake of cadmium (II ) ion s by Pleurotusus ostreatus biosorbent was 5.08 mg/g at 60 mg/L of cadmium (II) ion s concentrations. The Langmuir isotherm mod el fits significantly better experimental data than the Freundlich isotherm and BET isotherm model. Kinetic studies indicate that cadmium removal using Pleurotus ostreatus biosorbent follows electroplating wastewater than from synthetic wastewater. The findings indicated promising biosorption of cadmium using Pleurotusus ostreatus as biosorbent. Keywords : Biomass: Biosorption: Cadmium: Pleurotus oustreatus